2022
DOI: 10.1186/s12882-022-02930-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of bumetanide plus chlorthalidone on hypertension and volume overload in patients with chronic kidney disease stage 4–5 KDIGO without renal replacement therapy: a double-blind randomized HEBE-CKD trial

Abstract: Background The co-administration of loop diuretics with thiazide diuretics is a therapeutic strategy in patients with hypertension and volume overload. The aim of this study was to assess the efficacy and safety of treatment with bumetanide plus chlorthalidone in patients with chronic kidney disease (CKD) stage 4–5 KDIGO. Methods A double-blind randomized study was conducted. Patients were randomized into two groups: bumetanide plus chlorthalidone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…When primary focal segmental glomerulosclerosis develops further, it can lead to renal insufficiency and hypertension. The mechanisms of primary focal segmental glomerulosclerosis causing hypertension mainly involve: (I) the activation of the reninangiotensin system leads to the increase of renin-angiotensin secretion, resulting in hypertension (11)(12)(13); and (II) water and sodium retention due to renal insufficiency causes excessive blood volume, which leads to hypertension (14)(15)(16). Malignant hypertension can also promote glomerular filtration rate decline, atrophy of renal tubules, and renal interstitial fibrosis, leading to the development of end-stage renal disease and eventually forming a vicious circle (17).…”
Section: Discussionmentioning
confidence: 99%
“…When primary focal segmental glomerulosclerosis develops further, it can lead to renal insufficiency and hypertension. The mechanisms of primary focal segmental glomerulosclerosis causing hypertension mainly involve: (I) the activation of the reninangiotensin system leads to the increase of renin-angiotensin secretion, resulting in hypertension (11)(12)(13); and (II) water and sodium retention due to renal insufficiency causes excessive blood volume, which leads to hypertension (14)(15)(16). Malignant hypertension can also promote glomerular filtration rate decline, atrophy of renal tubules, and renal interstitial fibrosis, leading to the development of end-stage renal disease and eventually forming a vicious circle (17).…”
Section: Discussionmentioning
confidence: 99%
“…Data from patients with heart failure showed that diuretic combinations such as loop diuretic with a thiazide diuretic or with acetazolamide have proven their efficiency. Also, combined diuretics seem to be effective in patients with advanced chronic kidney disease or even nephrotic edema, but on the latter, there is only one RCT published so far [18][19][20][21]. Therefore, the aim of our study was to assess the non-inferiority and safety profile of the oral combination of furosemide/hydrochlorothiazide/amiloride compared to i.v.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2021 KDIGO guidelines, the selection of antihypertensive drugs is recommended to start with monotherapy for those over 75 years of age, and to sequentially combine ACEI or ARB with a thiazide-based diuretic (loop diuretics for advanced CKD) or CCB 2) . Considering the risk of thiazide induced hyponatremia, chlorothalidone had good clinical results for lowering blood pressure in advanced CKD patients 33) , however, the enrolled mean age was below 60 years old (HEBE-CKD trial) even if it was RCT study 34) . In other studies, chlorthalidone was associated with a greater incidence of hypokalemia and hyponatremia of equal dose compared with thiazide, therefore we consider to follow up the electrolyte for a while 35 36) .…”
Section: Introductionmentioning
confidence: 99%